World Saving - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2014)
This paper presents new evidence on the behavior of saving in the world, by extending previous empirical research in five dimensions. First, it is based on a very large and recent database, covering 165 countries from 1981 to 2012. Second, it conducts a robustness analysis across different estimation techniques. Third, the empirical search is expanded by including potential saving determinants identified by theory but not previously considered in the empirical literature. Fourth, the paper explores differences in saving behavior nesting the 2008-10 crisis period and four different country groups. Finally, it also searches for commonalities and differences in behavior across national, private, household, and corporate saving rates. The results confirm in part existing research, shed light on some ambiguous or contradictory findings, and highlight the role of neglected determinants. Compared to the literature, we find a larger number of significant determinants of saving rates, using different estimators, for different periods and country groups, and for different saving aggregates.